EFFECTIVENESS OF CHEST FREEZER GRANTS FOR PROCESSING AND MARKETING GROUP OF FISHERIES PRODUCTS IN TANAH LAUT REGENCY, INDONESIA - Mahmud J.; Hidayat A.S.; Agusliani E. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The Government of Tanah Laut Regency through the Food Security and Fisheries Service as a technical agency that handles as well as a supervisory agency in the field of processing marine and fishery products has provided grants for production facilities for processing fishery products in the form of chest freezers with a capacity of 330 L for 12 groups of fishery product processors and marketers. The aim of this research is to analyze the effectiveness of granting chest freezers to processors and marketers of fishery products in Tanah Laut Regency.